Evaluation of post-COVID depression, anxiety and stress among hemodialysis patients from an urban centre of Bangladesh (BIRDEM Medical Journal, 2024)
Background: Psychological effects of COVID-19 have been documented in different studies. Patients with endstage renal disease (ESRD) on regular hemodialysis are more vulnerable to this effect due to economic and social burden attached to their co-morbidities. This study was designed to evaluate degree of depression, anxiety and stress in patients on maintenance hemodialysis who were COVID-19 survivors and compare it with those who never had COVID-19.Methods: It was an observational study conducted among patients of ESRD getting regular hemodialysis on outdoor basis in Square Hospital. Total 156 patients were included in the study who were divided into two groups, 52 patients getting regular hemodialysis who suffered from COVID-19 in the year before study period (October, 2021 to March, 2022) were selected as COVID group and 104 age and sex matched patients of ESRD taking maintenance hemodialysis, who never had COVID-19 were taken as the non-COVID group. Data were collected via face-to-face interview and was recorded in a pre-formed two-part questionnaire with one part containing patient’s demographic characteristics and the other part included the 21 questions in accordance with depression, anxiety stress scale 21 (DASS21) scale to measure the degree of depression, anxiety and stress in that individual patient.Results: According to DASS21 score, prevalence of anxiety (75% versus 37.7%, P value 0.009), depression (62.5% versus 27.4%, P value 0.008) and stress (67.3% versus 40.6%, P value 0.01) in COVID group was higher than non-COVID group. Prevalence of mild and severe depression in COVID group was higher than non-COVID group. Prevalence of moderate, severe and extremely severe anxiety and all degrees of stress (mild, moderate, severe and extremely severe) were significantly higher in COVID group than non-COVID group.Conclusion: Psychological burden was significantly higher among ESRD on maintenance hemodialysis following COVID-19 than similar patients who did not previously suffer from COVID-19.BIRDEM Med J 2024; 14(2): 81-86